EKSPLORASI HAKIKAT FILOSOFIS DAN PRAKTIS ALAT PENDIDIKAN MODERN: KAJIAN MIXED METHOD TENTANG PERSEPSI GURU DAN HASIL BELAJAR SISWA - Dwinova Indhira Putri; Babang Robandi; Fitri Dwi Indriyani (STKIP Subang, 2025)
This mixed-method study explores the philosophical essence and practical implications of modern educational tools through examining teacher perceptions and student learning outcomes. The research addresses fundamental questions about how technology reshapes teacher-student relationships, transforms learning epistemology, and redefines educational objectives in contemporary pedagogy. Employing an explanatory sequential design, the study involved 45 students from SDN Tunas Jaya selected through purposive sampling. Quantitative analysis utilized structured tests and observations to measure cognitive achievement, while qualitative inquiry employed in-depth interviews with teachers to investigate their philosophical understanding and practical experiences. Results demonstrate significant improvement in student learning outcomes, with mean scores increasing from 72.4 to 83.6, and standard deviation decreasing from 8.2 to 6.1, indicating enhanced consistency across diverse learner abilities. Paired sample t-test yielded significance value of 0.000, confirming statistically meaningful differences. Qualitative findings reveal teacher awareness of paradigmatic shifts from knowledge transmitters to learning facilitators who mediate active knowledge construction. Thematic analysis identified three convergent themes regarding technological integration in education. Data triangulation establishes positive correlation between teachers' philosophical comprehension and learning effectiveness, confirming that technology serves as effective catalyst only when supported by robust pedagogical foundations. The study concludes that successful implementation of modern educational tools requires integrating technical competence with deep philosophical understanding, creating synergy between technological innovation and pedagogical wisdom in twenty-first century learning contexts.